Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0089390
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Tax Oncoprotein Inhibits the Estrogen-Induced-ER α-Mediated BRCA1 Expression by Interaction with CBP/p300 Cofactors

Abstract: BRCA1 is a multifunctional tumor suppressor, whose expression is activated by the estrogen (E2)-liganded ERα receptor and regulated by certain recruited transcriptional co-activators. Interference with BRCA1 expression and/or functions leads to high risk of breast or/and ovarian cancer. Another multifunctional protein, HTLV-1Tax oncoprotein, is widely regarded as crucial for developing adult T-cell leukemia and other clinical disorders. Tax profile reveals that it can antagonize BRCA1 expression and/or functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…[26][27][28][29] Therefore, we speculate that if expressed in breast cells, Tax would be able to block the expression and most of the activities of BRCA1. This speculation is supported by our previous study, 62 which show, for the first time, that Tax inhibits basal and E2-stimulated BRCA1 expression in breast cells by preventing the binding of ER-a transcriptional complex to BRCA1 promoter. It thus appears likely that in breast cells Tax can potentially create a BRCA1-deficient microenvironment that usually leads to breast cancer development.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…[26][27][28][29] Therefore, we speculate that if expressed in breast cells, Tax would be able to block the expression and most of the activities of BRCA1. This speculation is supported by our previous study, 62 which show, for the first time, that Tax inhibits basal and E2-stimulated BRCA1 expression in breast cells by preventing the binding of ER-a transcriptional complex to BRCA1 promoter. It thus appears likely that in breast cells Tax can potentially create a BRCA1-deficient microenvironment that usually leads to breast cancer development.…”
Section: Introductionsupporting
confidence: 53%
“…3.1 Effect of HTLV-1 Tax varients on the E2-induced BRCA1-Luc and ERE-Luc expression. In extention to our previous findings 62 which proved the potential of HTLV-1 Tax protein to significantly prevent the E2 induced BRCA1 expression, we examined in this study the effect of HTLV-1 Tax on the E2 induced expression of genes controlled by promoters containing the ERE sequences in comparison with its effect on BRCA1 expression. This was done by examining the effect of Taxexpressing vector on the expression of ERE-Luc or BRCA1-Luc in MCF-7 cells.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, Satake et al (2012) reported that the number of HTLV-1 carriers has decreased 10% over the past 2 decades (1980s to 2000s), so the age distribution of carriers has trended Tax1 has been reported to promote cancer cell proliferation via the Ras-Raf-MEK-ERK signaling pathway (Song et al, 2009). In addition, Tax1 sensitizes breast cancer cells to malignant transformation induced by environmental carcinogens through the inhibition of estrogen-induced ERα-mediated BRCA1 expression (Shukrun et al, 2014). Thus, we hypothesized that HTLV-1 infection is associated with breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Tax‐mediated BRCA1 inhibition provides information regarding the relationship between HTLV‐1 infection and the development of breast cancer because of the importance of BRCA1 as a predisposing factor in this disease. HTLV‐1 infection and penetration into breast cells are speculated to play a positive role in mammary tumorigenesis .…”
Section: Human T‐cell Lymphotropic Virusmentioning
confidence: 99%